The Influence of Perception and Motivation on the Interest of Accounting Study Program Students in Pursuing a Career in Taxation (Study on Accounting Students of the Faculty of Economics, Adventist University of Indonesia in 2019-2021) - Grace Melani Telaumbanua; Paul Eduard Sudjiman (Jurnal Pengetahuan dan Pendidikan, 2024)
This research was conducted to satisfy researchers' curiosity regarding the influence of perception and motivation on the interest of accounting students of the Faculty of Economics, Adventist University of Indonesia in 2019-2021 for a career in taxation. This research uses the Quantitative Descriptive method and the data obtained comes from a questionnaire which then the data is processed with the help of the SPSS version 22 application. Researchers used the population in this study, namely accounting students of the Adventist University of Indonesia during the 2019-2021 period, using the purpose sampling method and calculated using the slovin formula so that the number of samples obtained was 75 students of the Accounting study program. In analyzing this study, researchers used descriptive statistics, classical assumption tests, multiple linear regression and coefficient of determination. Through the research conducted, results were obtained that showed that partially perception has a positive effect on the interest in acting in the field of taxation as well as motivation has a significant influence on career interest in taxation. At the same time, perception and motivation have a great influence on the tax career interests of accounting students of Universitas Advent Indonesia